2010
DOI: 10.1007/s00277-009-0889-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance against PKC412 in resistant FLT3-ITD positive human acute myeloid leukemia cells

Abstract: Treatment of acute myeloid leukemia (AML) remains challenging with many patients harboring unfavorable prognostic parameters such as FLT3 internal tandem duplication (FLT3-ITD) mutations leading to a constitutively activated FLT3-receptor tyrosine kinase (RTK). Activation of proteins by phosphorylation of tyrosine residues is a common mechanism in leukemia development. Therefore, specific tyrosine kinase inhibitors (TKI) have been developed for AML therapy and are currently under investigation. The staurospori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 45 publications
4
45
0
Order By: Relevance
“…89,90 In clinical trials, it has been shown that FLT3-TKI treatment and myelosuppressive chemotherapy may induce an increase in FL expression and/or FLT3 cell surface expression. 52, 91 An alternative mechanism of resistance is activation of compensatory pathways rendering FLT3-mutated cells independent of FLT3 signaling.…”
Section: Secondary Resistancementioning
confidence: 99%
“…89,90 In clinical trials, it has been shown that FLT3-TKI treatment and myelosuppressive chemotherapy may induce an increase in FL expression and/or FLT3 cell surface expression. 52, 91 An alternative mechanism of resistance is activation of compensatory pathways rendering FLT3-mutated cells independent of FLT3 signaling.…”
Section: Secondary Resistancementioning
confidence: 99%
“…In addition, blocking FLT3 ligand with an FLT3 ligand-neutralizing antibody was observed to enhance the proapoptotic activity of ABT-869 against ABT-869-resistant cells (Zhou et al, 2009). Another study of resistance in MV4-11 cells made resistant to PKC412 revealed acquisition of clonal alternations at chromosome 13q, additional FLT3 signaling, and changes in gene expression before and after treatment with PKC412, including that of FLT3 ligand (Stolzel et al, 2010).…”
Section: Gain-of-function Mutations In Cblmentioning
confidence: 99%
“…Aberrant expression of antiapoptotic proteins is another mechanism of resistance to FLT3 inhibitors. For example, increased protein levels of the inhibitor of apoptosis (IAP), survivin, as well as activation of STAT1, STAT3 and STAT5, were observed in ABT-869-resistant MV4-11 cells (Zhou et al, 2009), and antiapoptotic proteins were upregulated in PKC412-resistant MV4-11 cells (Stolzel et al, 2010). Similarly, overexpression of antiapoptotic proteins of the BCL2 family has been found to mediate resistance to FLT3 inhibition in hematopoietic cells with activating FLT3 mutations Mechanisms of resistance to FLT3 inhibition E Weisberg et al (Kohl et al, 2007) and the antiapoptotic protein, MCL-1, was observed to be induced by a non-juxtamembrane ITD that has integrated into the b-2 sheet of the first kinase domain (FLT3_ITD627E) (Brietenbuecher et al, 2009).…”
Section: Aberrant Activation Of Growth and Viability Pathwaysmentioning
confidence: 99%
“…Mutations or expression modification of genes regulating apoptosis, such as BCL2, MCL-1, and NF-jB, can render leukemic cells independent of FLT3 signaling [86,[95][96][97]. In an in vitro model, midostaurin resistance appeared to be in part governed by up-regulation of anti-apoptotic signals and down-regulation of pro-apoptotic pathways [98].…”
Section: Receptor-intrinsic Mechanisms Of Resistancementioning
confidence: 99%